2021
DOI: 10.4067/s0718-221x2021000100465
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of charcoal origin based on deep learning

Abstract: The differentiation between the charcoal produced from (Eucalyptus) plantations and native forests is essential to control, commercialization, and supervision of its production in Brazil. The main contribution of this study is to identify the charcoal origin using macroscopic images and Deep Learning Algorithm.We applied a Convolutional Neural Network (CNN) using VGG-16 architecture, with preprocessing based on contrast enhancement and data augmentation with rotation over the training set images. on the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nowadays, the methods for identifying the origin of food or medicinal materials mainly include artificial naked eye recognition [ 4 ], chemical composition analysis [ 5 , 6 , 7 , 8 , 9 ], near-infrared spectral analysis [ 10 , 11 , 12 ], image recognition, and other methods [ 13 , 14 , 15 ]. The traditional artificial naked eye method has low identification efficiency, and the screening results are affected by subjective factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the methods for identifying the origin of food or medicinal materials mainly include artificial naked eye recognition [ 4 ], chemical composition analysis [ 5 , 6 , 7 , 8 , 9 ], near-infrared spectral analysis [ 10 , 11 , 12 ], image recognition, and other methods [ 13 , 14 , 15 ]. The traditional artificial naked eye method has low identification efficiency, and the screening results are affected by subjective factors.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer vision and machine learning technology, many researchers have established an image-based origin identification model to identify the origin of food or medicinal materials by collecting images of samples and conducting training and learning. De et al have identified charcoal sources using macro images and deep learning algorithms [ 13 ]. Wang et al have used the methods of image and visual information and machine learning to intelligently identify the origin of Angelica [ 14 ].…”
Section: Introductionmentioning
confidence: 99%